The Development of Student Team Achievement Division Online Learning Tools to Improve Students' Analytical Ability - Syifa, Ummi Layyinatusy; Utami, Nur Rahayu (Journal of Biology Education, 2021)
Analytical skills are thinking to solve issues with reasons and relate problems that arise with previous issues. This capability is one of the focus goals of 21st century education. A Covid-19 pandemic causes learning to take place online and remotely. Automatically learning devices must be made conditionally and accordingly. Teachers need to apply a learning model with appropriate learning resources, not only with conventional methods (lectures), to analyze the biology material presented. The learning model chosen to improve students' analytical skills was the Student Team Achievement Division (STAD). This study aimed to describe the characteristics and analyze the feasibility level of developing the STAD Model online learning tool. The research design used a modified Research and Development (R&D) method. The research was carried out online at the Odd Semester of the Academic Year of 2020/2021. The subjects in this study were 15 students of twelve graders of Mathematics and Natural Sciences. They have received material on Human Reproductive Systems and 2 Biology Teachers at SMA N 1 Dempet. The research’s object was online learning tools in the form of syllabus, lesson plan one sheet, and worksheets based on the STAD learning model of Human Reproductive System Material. The data analyzed descriptively, qualitatively, and quantitatively. Data analysis techniques included validation questionnaires by validators and analysis of students’ and teachers’ readability of learning devices. The results showed that the characteristics of the learning tools developed in this study were online syllabus, lesson plans, and worksheets; STAD Model-Based; RPP one sheet. The materials presented were Human Reproductive System Material; The learning objectives were equipped with audience and behaviour elements and had a mission to improve students' analytical skills. The analysis results showed that the developed syllabus and lesson plans were considered very valid, with a percentage of 94.2% and 95%. The student worksheet (LKS) was included very valid criteria in terms of material with a percentage of 89% and terms of media by 85%. The readability questionnaire results showed that the average percentage of teacher’s responses was 93% and student’s responses were 79%. It concluded that the STAD Model online learning tool to improve students' analytical skills was included in the very valid criteria and very suitable for use in the biology learning process of Human Reproductive System Material.